Case Report: The rare pancreatic involvement in Erdheim-Chester disease - Li, Ji; Zhang, Ming; Zou, Yadan; Zhang, Jing; Song, Juanjuan; Li, Ting; Li, Sheng-Guang (Frontiers in Immunology, 2025)
BackgroundErdheim-Chester disease (ECD) is an exceedingly rare non-Langerhans histiocytosis. While often affecting the skeleton, cardiovascular system, and kidneys, pancreatic involvement remains uncommon and can mimic more prevalent conditions such as autoimmune or chronic pancreatitis.Case PresentationA 58-year-old female presented with a two-year history of bilateral lower limb edema and a year-long course of recurrent abdominal pain. Imaging suggested necrotizing pancreatitis and retroperitoneal infiltration, yet serum IgG4 levels were normal. A CT-guided biopsy of the pancreas and retroperitoneum revealed diffuse proliferation of foamy histiocytes (CD68+, CD163+, CD1α-) carrying the BRAF V600E mutation, confirming ECD. Supportive therapy and corticosteroids temporarily relieved symptoms, but targeted treatment was delayed due to the COVID-19 pandemic. Subsequent follow-up revealed significant clinical improvement following targeted therapy.DiscussionECD can present with non-specific clinical features, leading to frequent misdiagnoses. Involvement of the pancreas, as demonstrated here, is particularly rare. The discovery of the BRAF V600E mutation underscores the importance of molecular testing for both diagnostic confirmation and therapeutic stratification. The immunopathogenesis of ECD involves activated macrophages and aberrant MAPK signaling, which drive chronic inflammation and tissue fibrosis.ConclusionThis case highlights the diagnostic challenges of pancreatic ECD and underscores the critical value of an integrated approach—including imaging, immunohistochemistry, and molecular analysis—in achieving timely diagnosis. Early recognition and targeted therapy may significantly improve outcomes for patients with BRAF-mutant ECD.